PERILAKU FONEM DALAM BAHASA ARAB DAN IMPLIKASINYA TERHADAP MAKNA - Achmad Khusnul Khitam (Sunan Kalijaga State Islamic University Yogyakarta, 2015)
This research aims to study phoneme’s behaviour on Arabic words and to discover the relation between voice and its meaning. Phoneme, as the smallest contrastive linguistic unit, has a huge influence on bringing a change of meaning. The preference of certain phoneme on a word may produce certain meaning inside it. Therefore, a singel word with different phonemes produces different meaning. This research based on library research, a research proceed by gathering some facts from various books, articles, and other literatures related to the subject. This research combines semantical approach and phonological approach with analytic description method. This research finds that Arabic words use certain phoneme to express certain meaning; phonemes with heavy articulations are often used to express serious meanings, and phonemss with light articulations are often used to express trivial meanings. It is also found that phoneme articulation has many patterns, such as plosive articulation, nasal articulation, fricative articulation, trill, lateral, etc.